Project Work Writing in BBS Fourth Years Course: Procedures and Practices - Sharma, Puspa Raj (Journal of Nepalese Business Studies, 2018)
This paper has been prepared with an objective to provide the guidelines to the BBS students to write the project work and teachers to guide their students in writing the project work and preparing the paper has included procedure of project work assignment prescribed by Office of the Dean, Faculty of Management, Tribhuvan University. The paper give some insight on necessary procedures of the submission of project work writing. It also give some practical insight to the faculty members who involved in the supervision. The Journal of Nepalese Business Studies Vol. X No. 1 December 2017, Page : 1-7